فاعلية الخدمات الإشرافية المقدمة للمرشدين التربويين العاملين في المدارس الحكومية في فلسطين من وجهة نظرهم - محاميد، فايز عزيز محمد (جامعة القدس المفتوحة, 2016)
The aim of this study is to investigate the effectiveness of supervisory services provided to school counselors at governmental schools in Palestine from their perspectives. The sample of this study consisted of (170) male and female counselors, selected randomly and represented around (22%) of all school counselors in Palestine totaling (756) male and female counselors. For the purpose of this study, Supervisory Services Scale was constructed and used. The results indicated the effectiveness of supervision services. The total score of the supervisory scale was (4.39), which is a very high degree. The result showed that there are no significant differences in supervisory services due to the study variables: Gender, academic level and years of experiences. Based on the results of this study the researcher recommends studying other aspects of supervisory process such as: Supervisory skills, techniques and methods of supervision and supervision models used in school counseling. I hope other researchers will conduct studies to find out the effectiveness of supervisory services at counseling, psychotherapy and mental health centers.
هدفت الدراسة الحالية إلى التعرف إلى فاعلية الخدمات الإشرافية المقدمة للمرشدين التربويين العاملين في المدارس الحكومية في فلسطين من وجهة نظرهم، وقد تكونت عينة الدراسة من (170) مرشدا ومرشدة اختيروا بالطريقة العشوائية البسيطة، إذ مثلوا بذلك ما نسبته (22%) من المرشدين التربويين العامليين في المدارس الحكومية في فلسطين، والبالغ عددهم (756) مرشدا ومرشدة. وقد استخدمت الدراسة مقياس فاعلية الخدمات الإشرافية الذي بني وصمم لأغراض الدراسة الحالية. أظهرت النتائج فاعلية مرتفعة جدا للخدمات الإشرافية المقدمة للمرشدين التربويين، إذ بلغت الدرجة الكلية لمقياس الخدمات الإشرافية (4.39)، وهي درجة مرتفعة جداً، كما لم تظهر النتائج أية فروق ذات دلالة إحصائية في الخدمات الإشرافية تبعا لمتغيرات الدراسة المختلفة، وهي: الجنس، والمؤهل العلمي، وسنوات الخبرة. وبناء على نتائج الدراسة، فإن الباحث يوصي بضرورة القيام بدراسات بحثية تستهدف فحص جوانب مختلفة من العملية الإشرافية، كالمهارات الإشرافية، وفنيات وأساليب الإشراف، والنماذج الإشرافية التي يستخدمها المشرفون في الإرشاد المدرسي، والقيام بدراسات بحثية تهدف التعرف إلى فاعلية الخدمات الإشرافية المقدمة في مراكز الإرشاد والعلاج النفسي والصحة النفسية العاملة في فلسطين.
Keywords: المدارس الحكومية; فلسطين; المرشدين التربويين; الخدمات الإشرافية